Rancang Bangun Mesin Penyaring Ukuran Ikan Teri Semi Otomatis - Gocal Pauwa; Bambang Bambang; Sandi Rais; Amat Umron; Syamsul Bahri LM (Patria Artha Technological Journal, 2022)
Research on the design of an anchovy filter machine was carried out with the aim of designing a fish-size ring machine using a capacity dynamo and a dimmer as a regulator of movement speed and fish. The design is made with specifications for the size of iron as a framework, with a height of 745 mm, a width of 430 mm, and a length of 800 mm. There are two sizes of fish measuring at the top and 1/6 inch at the bottom. The engine uses a 2200 Volt dynamo and a dimmer. From the results of the dynamo rotation speed test, the rotational speed produced by pulley 1 is greater than pulley 2. The difference in rotational speed on pulley one and pulley two is caused by a change in the transmission system with the addition of a fan belt between pulley 1 and pulley 2. The rotation produced by the rotation of pulley 1 is a rotation that is directly connected to the dynamo so that the number of rotations will be greater. While the rotation produced by pulley 2 is the rotation of the transmission system. Puli 2 will rotate to move the axle, which is connected to the Pillow Block. Measurement of dynamo flow and voltage is carried out to see how much rotation mode on the dimmer will be used to speed up or slow down the rotation of the dynamo. The small size of the dynamo that is used causes the dimmer mode that is used to start at mode 7 on a scale of 1-9 modes contained in the dimmer.